2017
DOI: 10.1089/rej.2016.1816
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Skeletal Muscle in Aged Rats Following High-Intensity Stretch-Shortening Contraction Training

Abstract: Exercise is the most accessible, efficacious, and multifactorial intervention to improve health and treat chronic disease. High-intensity resistance exercise, in particular, also maximizes skeletal muscle size and strength-outcomes crucial at advanced age. However, such training is capable of inducing muscle maladaptation when misapplied at old age. Therefore, characterization of parameters (e.g., mode and frequency) that foster adaptation is an active research area. To address this issue, we utilized a rodent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…It should be mentioned at the fundamental level that these skeletal muscle contractions typically have been investigated using isolated preparations; although there are limitations to the physiological translation of these types of models and investigations, they have produced a wealth of essential data [63][64][65]. In addition, there are groups, including ours, that implement skeletal muscle contractions in a model that is more physiologically relevant in that it combines all types of skeletal muscle contractions as they are conducted and utilized in vivo: this scenario is known as either SSCs [12,13,[66][67][68] or a subcategory of the SSCs defined as the stretch-shortening cycle [11,[69][70][71][72]. The nuance and distinction between these two independently combined contraction paradigms is that as the SSCs include and incorporate the sequential pre-activation of the isometric contraction followed by successive lengthening and shortening contractions, and these SSCs are incurred during all activities of daily movement in mammals [50].…”
Section: Sscs As "Resistance-type Exercise" Training (Rtet)mentioning
confidence: 99%
See 4 more Smart Citations
“…It should be mentioned at the fundamental level that these skeletal muscle contractions typically have been investigated using isolated preparations; although there are limitations to the physiological translation of these types of models and investigations, they have produced a wealth of essential data [63][64][65]. In addition, there are groups, including ours, that implement skeletal muscle contractions in a model that is more physiologically relevant in that it combines all types of skeletal muscle contractions as they are conducted and utilized in vivo: this scenario is known as either SSCs [12,13,[66][67][68] or a subcategory of the SSCs defined as the stretch-shortening cycle [11,[69][70][71][72]. The nuance and distinction between these two independently combined contraction paradigms is that as the SSCs include and incorporate the sequential pre-activation of the isometric contraction followed by successive lengthening and shortening contractions, and these SSCs are incurred during all activities of daily movement in mammals [50].…”
Section: Sscs As "Resistance-type Exercise" Training (Rtet)mentioning
confidence: 99%
“…It is chronic resistance exercise loading, or training, that is unique in promoting restoration or improvements in skeletal muscle performance (i.e., strength, work capacity, fatigue resistance, etc.) and skeletal muscle mass [83,84], as evidence for these findings exist in both human [57,71,83] and animal studies [66]; yet, little evidence exists for improving skeletal muscle quality in various populations, including aged populations [7,59]. There are numerous human studies that have suggested that resistance exercise training is beneficial in countering distinct components of musculoskeletal health and aging [71,83,84]; however, no translational study has shown that resistance exercise training can restore musculoskeletal health with aging to youthful states entirely.…”
Section: Efficacy Of Ssc Rtet In Restoring the Youthful Phenotypementioning
confidence: 99%
See 3 more Smart Citations